KONSEP SOP UNTUK PENANGANAN PASCAPANEN MANGGA Cv. GEDONG UNTUK TUJUAN EKSPOR - Kun Tanti Dewandari; Ira Mulyani; Dondy A Setyabudi (Badan Standardisasi Nasional, 2009)
Mango is priority commodities in agribussines development. Production that overflow in 2006 achieve 1.621.997million ton with total land harvest 195.503 hectare has potential to developed especially for market exports. Oneof this is gedong mango. Now, volume exports of Indonesian mango only 0,22% from total export, in other sideIndonesia is sixth biggest country mango production in the world. This is caused by quality rules very tight fromexporter country and there is not procedure operational standard (SOP) mango handling from farmer up to readyexport to be barrier for marketing. Research from BB - Pascapanen in 2007 that does handling technology testgedong mango to export can be based for standard operational procedure. With this SOP, can increase qualityand volume export mango gedong. Research shows that handling postharvest process mango gedong to exportincluded harvest with stalk 10 - 15mm, sortasi and grading, waxing with concentration 6%, benomyl 1000ppm andglossy agent 0,125%, packaging with net foam and carton box, temperature adaptation 15°C, 24 hours withstorage in temperature 10°C. With this process during storage 3 weeks, fruits still fresh, expose at temperature 18- 20°C and ripe on weeks 6. During 4 weeks, fruit begins attacked postharvest disease with percentage 20 - 50%.